Acute Kidney Injury in High-Risk Patients in Cardiac Surgery of Coronary Artery Disease - Olena Gogayeva; Anatoliy V. Rudenko; Vasyl V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2021)
The aim. To analyze the features of the perioperative period in high-risk patients with coronary artery disease (CAD) and postoperative acute kidney injury (AKI).Materials and methods. A post-hoc analysis of 354 high-risk patients with various forms of CAD who were operated and discharged from the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine from January 2009 till December 2019. All the patients underwent clinical and laboratory tests, ECG, echocardiography, coronary angiography, ventriculography and surgical myocardial revascularization with correction of concomitant cardiac pathology. Based on serum creatinine, the glomerular filtration rate (GFR) was calculated based on CKD-EPI equation on admission, on day 1 after surgery and at discharge.Results. On admission, 132 (37.2%) patients had chronic kidney disease (CKD) with GFR <60 ml/min/1.73 m2. Postoperative AKI occurred in 10 (2.8%) patients, with a predominance of patients with complicated forms of CAD (p = 0.0249), type 2 diabetes mellitus (p = 0.0109). There was no dependence of the occurrence of AKI on age (p = 0.6755), the initial stage of CKD (p = 0.4601) and the Charlson comorbidity index (p = 1.0000). However, AKI more often developed during on-pump operations (p = 0.0333) using cardioplegia (p = 0.0164) and was associated with longer duration (p = 0.0007) and higher blood loss (p = 0.0001). In the early postoperative period, patients with AKI more often developed acute heart failure (p = 0.0051), anemia (p = 0.0176) and were characterized by a longer length of stay in the intensive care unit (p = 0.0010) and at the Institute after surgery (p = 0.0363).Conclusions. Perioperative prevention of nephrological complications involves limitation of the use of nephrotoxic drugs, compensation of comorbid conditions and reduction of intraoperative ischemic time.